New magnetotelluric data trough the boundary between the Ossa Morena and Centroiberian Zones - Gerard Muñoz Soler; Wiebke Heise; C. Paz; E. Almeida; Fernando Monteiro Santos; Jaume Pous i Fábregas (Geologica Acta, 2005)
The south-western part of the Iberian Peninsula, including the southern branch of the Iberian Massif, has recently been the subject of several magnetotelluric (MT) studies. This area is made up of three different tectonic terranes: the South Portuguese Zone (SPZ), the Ossa Morena Zone (OMZ) and the Central Iberian Zone (CIZ). The boundaries between these zones are considered to be sutures, which appear as high electrical conductivity anomalies in the MT surveys. The OMZ is characterised by a conductive layer at middle-lower crustal levels. To investigate the continuity of this conductive layer into the CIZ, a new MT profile was carried out. This 75-km long ENE profile goes through the boundary between the OMZ and the CIZ. The results of a two-dimensional magnetotelluric inversion revealed a high-conductivity anomaly in the transition OMZ/CIZ (the so-called Central Unit), which is interpreted as due to interconnected graphite along shear planes. High-conductivity anomalies appeared in the middle crust of the CIZ, whose geometry and location are consistent with the conductive layer previously found in the OMZ, thus confirming the prolongation of the conductive layer into the CIZ. The top of this layer correlated spatially with a broad reflector detected by a seismic profile previously acquired in the same area. This, together with other geological and petrological evidence, points to a common origin for both features.